Implementation of Maqashid Shariah Principles in Underwriting Surplus Allocation: Systematic Literature Review - Jhody Wiraputra; Okta Sari; Rima Yustina (International Publisher, 2025)
This study aims to map and synthesize the implementation of Maqashid Shariah principles in underwriting surplus allocation policies in the Islamic insurance industry. Using a qualitative approach with a systematic literature review (SLR) method that follows PRISMA guidelines, the study analyzed 74 data sources from the 2015-2025 time frame, including journal articles, fatwas, and international standards such as AAOIFI and IFSB. The findings reveal the transformation of surplus management from formal compliance to broader integration of social values, such as the use of surplus for micro-takaful subsidies and alignment with the Sustainable Development Goals (SDGs). Despite the jurisprudential debate over the operator's right to surplus as a performance bonus (Ju'alah) as well as transparency challenges resulting from the implementation of IFRS 17, this study confirms that Maqashid Shariah serves as an ethical compass to ensure justice (iqamah al-adl) and protection of property (hifz al-mal). The implication is that regulators and practitioners need to adopt digital technologies such as blockchain to improve accountability for surplus distribution and reposition the role of operators as architects of public benefit for the sustainability of the Islamic financial ecosystem.